Pengaruh Media Simulasi PhET terhadap Keaktifan Belajar IPAS Kelas V SDN 67 Parepare - Usman Usman; Hj. Nurul Mukhlisa; Marsha Banda Naira (MASALIQ, 2026)
Student learning engagement is an important factor in determining the success of Natural and Social Sciences (IPAS) learning in elementary schools, but students’ low active participation remains a challenge in the learning process. This study aimed to analyze the effect of using PhET simulation media on students’ learning engagement in fifth-grade IPAS learning at UPTD SD Negeri 67 Parepare. The study employed a quantitative approach using a quasi-experimental method and a posttest-only control group design. The research sample consisted of 43 students selected through purposive sampling, comprising 23 students from Class V.A as the experimental group and 20 students from Class V.B as the control group. Data were collected through observations and a learning engagement questionnaire and were subsequently analyzed using descriptive statistics and an independent-samples t-test. The results showed that students who participated in learning using PhET simulation media had a higher level of learning engagement than students in the control group. The independent-samples t-test yielded a two-tailed significance value of less than 0.05, indicating a significant difference between the experimental and control groups. Thus, the use of PhET simulation media had a positive effect on students’ learning engagement in IPAS learning. These findings confirm that PhET simulation media can be used as an interactive learning medium to enhance students’ active participation and engagement in the IPAS learning process in elementary schools.